Response of Turkey Muscle Satellite Cells to Thermal Challenge. II. Transcriptome Effects in Differentiating Cells - Reed, Kent M.; Mendoza, Kristelle M.; Strasburg, Gale M.; Velleman, Sandra G. (Frontiers in Physiology, 2017)
Background: Exposure of poultry to extreme temperatures during the critical period of post-hatch growth can seriously affect muscle development and thus compromise subsequent meat quality. This study was designed to characterize transcriptional changes induced in turkey muscle satellite cells by thermal challenge during differentiation. Our goal is to better define how thermal stress alters breast muscle ultrastructure and subsequent development. Results: Skeletal muscle satellite cells were previously isolated from the Pectoralis major muscle of 7-wk-old male turkeys (Meleagris gallopavo) from two breeding lines: the F-line (16 wk body weight-selected) and RBC2 (randombred control line) were used in this study. Cultured cells were induced to differentiate at 38° C (control) or thermal challenge temperatures of 33° C or 43° C. After 48 h of differentiation, cells were harvested and total RNA was isolated for RNAseq analysis. Analysis of 39.9 Gb of sequence found 89% mapped to the turkey genome (UMD5.0, annotation 101) with average expression of 18,917 genes per library. In the cultured satellite cells, slow/cardiac muscle isoforms are generally present in greater abundance than fast skeletal isoforms. Statistically significant differences in gene expression were observed among treatments and between turkey lines, with a greater number of genes affected in the F-line cells following cold treatment whereas more differentially expressed (DE) genes were observed in the RBC2 cells following heat treatment. Many of the most significant pathways involved signaling, consistent with ongoing cellular differentiation. Regulation of Ca2+ homeostasis appears to be significantly affected by temperature treatment, particularly cold treatment. Conclusions: Satellite cell differentiation is directly influenced by temperature at the level of gene transcription with greater effects attributed to selection for fast growth. At lower temperature, muscle-associated genes in the satellite cells were among the genes with the greatest down regulation consistent with slower differentiation and smaller myotubes. Fewer expression differences were observed in the differentiating cells than previously observed for proliferating cells. This suggests the impact of temperature on satellite cells occurs primarily at early points in satellite cell activation.